Evaluating a novel approach to stimulate open science collaborations: a case series of "study-a-thon" events within the OHDSI and European IMI communities. Issue 4 (17th November 2022) - Hughes, N; Rijnbeek, P R; van Bochove, K; Duarte-Salles, T; Steinbeisser, C; Vizcaya, D; Prieto-Alhambra, D; Ryan, P
Abstract: Objective: We introduce and review the concept of a study-a-thon as a catalyst for open science in medicine, utilizing harmonized real world, observation health data, tools, skills, and methods to conduct network studies, generating insights for those wishing to use study-a-thons for future research. Materials and Methods: A series of historical study-a-thons since 2017 to present were reviewed for thematic insights as to the opportunity to accelerate the research method to conduct studies across therapeutic areas. Review of publications and experience of the authors generated insights to illustrate the conduct of study-a-thons, key learning, and direction for those wishing to conduct future such study-a-thons. Results: A review of six study-a-thons have provided insights into their scientific impact, and 13 areas of insights for those wishing to conduct future study-a-thons. Defining aspects of the study-a-thon method for rapid, collaborative research through network studies reinforce the need to clear scientific rationale, tools, skills, and methods being collaboratively to conduct a focused study. Well-characterized preparatory, execution and postevent phases, coalescing skills, experience, data, clinical input (ensuring representative clinical context to the research query), and well-defined, logical steps in conducting research via the study-a-thon method are critical. Conclusions: A study-a-thon is a focused multiday research event generating reliable evidence on a specific medical topic across different countries and health systems. In a study-a-thon, a multidisciplinary team collaborate to create an accelerated contribution to scientific evidence and clinical practice. It critically accelerates the research process, without inhibiting the quality of the research output and evidence generation, through a reproducible process. Lay Summary: The research process is generally time-consuming, requiring considerable efforts and resources and planning over an extended duration of time before its results, such as via publications. Meanwhile, patients, clinicians, and healthcare providers need evidence to support decision-making from individual treatment to populations and public health policy, and more quickly than we have been used to, to date. This article describes an approach to accelerating the research process, bringing together relevant research and clinical practitioners, whilst not undermining confidence in the research results. Within this article the research event, or study-a-thon, is described, using six examples since 2017, within an international research network, Observational Health Data Sciences and Informatics (OHDSI). These examples help illustrate the steps required to conduct a study-a-thon, the use of health data under the right conditions, and learning from this process for others to consider using study-a-thons to accelerate their own research process where relevant. For the authors and colleagues in the OHDSI network, the open nature of conducting research via study-a-thons can also ensure full transparency of the process for all involved, as well as being able to reproduce results more readily, a key principle in good scientific conduct.